Associations between use of expressed human milk at 2 weeks postpartum and human milk feeding practices to 6 months: a prospective cohort study with vulnerable women in Toronto, Canada - Cindy-Lee Dennis; Jane Francis; Alex Kiss; Deborah L O'Connor; Erica Di Ruggiero; Alison Mildon; Stacia Stewart; Bronwyn Underhill; Yi Man Ng; Christina Rousseau; Daniel W Sellen (BMJ Open)
Objectives To examine whether use of expressed human milk in the first two weeks postpartum is associated with cessation of human milk feeding and non-exclusive human milk feeding up to 6 months.Design Pooled data from two prospective cohort studiesSetting Three Canada Prenatal Nutrition Program (CPNP) sites serving vulnerable families in Toronto, Canada.Participants 337 registered CPNP clients enrolled prenatally from 2017 to 2020; 315 (93%) were retained to 6 months postpartum. Exclusions: pregnancy loss or participation in prior related study; Study B: preterm birth (<34 weeks); plan to move outside Toronto; not intending to feed human milk; hospitalisation of mother or baby at 2 weeks postpartum.Primary and secondary outcome measures Main exposure variable: any use of expressed human milk at 2 weeks postpartum. Outcomes: cessation of human milk feeding by 6 months; non-exclusive human milk feeding to 4 months and 6 months postpartum.Results All participants initiated human milk feeding and 80% continued for 6 months. Exclusive human milk feeding was practiced postdischarge to 4 months by 28% and to 6 months by 16%. At 2 weeks postpartum, 34% reported use of expressed human milk. Any use of expressed human milk at 2 weeks was associated with cessation of human milk feeding before 6 months postpartum (aOR 2.66; 95% CI 1.41 to 5.05) and with non-exclusive human milk feeding to 4 months (aOR 2.19; 95% CI 1.16 to 4.14) and 6 months (aOR 3.65; 95% CI 1.50 to 8.84).Trial registration numbers NCT03400605, NCT03589963.